2010
DOI: 10.1182/blood-2010-04-280925
|View full text |Cite
|
Sign up to set email alerts
|

Transcription profiling in human platelets reveals LRRFIP1 as a novel protein regulating platelet function

Abstract: Within the healthy population, there is substantial, heritable, and interindividual variability in the platelet response. We explored whether a proportion of this variability could be accounted for by interindividual variation in gene expression. Through a correlative analysis of genomewide platelet RNA expression data from 37 subjects representing the normal range of platelet responsiveness within a cohort of 500 subjects, we identified 63 genes in which transcript levels correlated with variation in the plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 44 publications
3
81
0
Order By: Relevance
“…These molecules in platelets may come from different sources, such as those inherited from megakaryocytes, those absorbed from the plasma, or those generated de novo. With regard to de novo synthesis of molecules in platelets, although platelets are anucleate, they express significant amounts of RNA, including mRNAs (e.g., premature and mature RNA), structural and catalytic RNAs (e.g., ribosomal and tRNA), regulatory RNAs (e.g., microRNA), and noncoding RNA (e.g., anti-sense RNA) (90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105). More recently, it also was revealed that platelets contain all of the molecular machinery to translate mRNA into proteins, and they have the ability to transfer RNA to recipient cells where it can regulate cellular function (101-104).…”
Section: Platelet Transcriptomicsmentioning
confidence: 99%
“…These molecules in platelets may come from different sources, such as those inherited from megakaryocytes, those absorbed from the plasma, or those generated de novo. With regard to de novo synthesis of molecules in platelets, although platelets are anucleate, they express significant amounts of RNA, including mRNAs (e.g., premature and mature RNA), structural and catalytic RNAs (e.g., ribosomal and tRNA), regulatory RNAs (e.g., microRNA), and noncoding RNA (e.g., anti-sense RNA) (90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105). More recently, it also was revealed that platelets contain all of the molecular machinery to translate mRNA into proteins, and they have the ability to transfer RNA to recipient cells where it can regulate cellular function (101-104).…”
Section: Platelet Transcriptomicsmentioning
confidence: 99%
“…Because platelets do not contain a nucleus, their RNA transcripts, needed for functional maintenance, are derived from megakaryocytes during platelet origination. 6,8,9 Platelet RNA can be readily isolated and subjected to gene-expression analysis. [8][9][10] Here we show that blood platelets take up tumor-derived secreted membrane vesicles that can contain tumor-associated RNA and that platelets can serve as a potential biomarker source for cancer diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] As part of this effort, we previously identified a panel of platelet membrane proteins that were expressed more highly in MKs and resting endothelial cells (ECs) than in other blood cell lineages, but with hitherto unknown roles in platelet function or thrombus formation. 6 Of the 279 genes identified, 4 (including bone morphogenetic protein and activin membrane-bound inhibitor [BAMBI]) were selected for functional analysis in zebrafish.…”
Section: Introductionmentioning
confidence: 99%